Could HoLEP change the further management of incidental prostate cancer? - Di Gianfrancesco, Luca; Crestani, Alessandro; Amodeo, Antonio; Corsi, Paolo; Miglioranza, Eugenio; De Marchi, Davide; Busetto, Gian Maria; Maggi, Martina; Porreca, Angelo (Frontiers in Urology, 2023)
Introduction Holmium laser enucleation of the prostate (HoLEP) is effective in treating lower urinary tract symptoms from prostatic disease. We investigated the role of HoLEP in the management of patients with benign prostatic hypertrophy (BPH) and prostate cancer (PCa). Materials and Methods Retrospective review of data regarding all patients undergoing HoLEP at a single institution was performed. Pre- and postoperative prostate-specific antigen, multiparametric magnetic resonance imaging, and pathology results were analyzed for those with PCa identified prior to HoLEP (group 1) and incidentally at HoLEP (group 2). Results A total of 147 patients underwent HoLEP. Eighteen patients had PCa diagnosed before HoLEP and 16 (10.9%) had PCa incidentally detected at HoLEP. The total prostate-specific antigen level at 3 months after HoLEP had dropped by 82.35% (8.27 ng/ml at initial evaluation to 1.46 ng/ml) in patients already diagnosed with PCa and by 91.03% (3.01 ng/ml at initial evaluation to 0.27 ng/ml) in the group with incidental detection; the values remained stable up to 12 months after HoLEP. All patients in both groups (including patients who underwent cancer treatment post-HoLEP) survived without cancer progression, including patients with PCa diagnosis at HoLEP and based on the initial PCa status.. Conclusions More than 10% of patients undergoing HoLEP might receive a diagnosis of PCa. HoLEP can be performed even in patients with PCa, at any disease stage, in order to relieve lower urinary tract symptoms. Whether PCa is diagnosed before or at HoLEP, the procedure does not affect the oncological outcomes. Further investigation is warranted to determine the durability of the success of these approaches.